Nietzsche e Guyau: egoísmo e altruísmo, uma interpretação de Alfred Fouillée - Castilho, Kelly de Fátima (2025)
This thesis examines Alfred Fouillée's interpretation of Friedrich Nietzsche's self-proclaimed immorality. In his work Nietzsche and Immoralism, Fouillée warns of the dangers and extravagances present in the doctrines of the German philosopher, proposing to combat his advances, especially on French soil. To indicate an alternative to Nietzschean thought, Fouillée presents the ideas of his young stepson — also a philosopher and poet — Jean-Marie Guyau, who developed quite original and serious notions in the field of morals. It is in this context that Fouillée establishes an opposition between Nietzsche and Guyau, calling on readers to take sides. On the one hand, there are Guyau's conceptions, which sustain the spontaneity of altruism and feelings such as generosity and sympathy; on the other, there is Nietzsche, representing selfishness and aggressiveness. Nietzsche's self-proclaimed immoralism is configured, from Fouillée's point of view, as a mere inversion of Christian values, substantiating an apology of values opposed to those preached by Christianity. Thus, Nietzsche would be, according to Fouillée, an "anti-Christian dogmatist", defender of values such as selfishness, aggressiveness, voluptuousness and anti-piety. The analysis of Fouillée's interpretation allows us to see that the interpreter's intention was not to understand or dialogue with Nietzsche's thought, but to judge and combat it. Interpretations of this nature, in our view, disregard Nietzsche's efforts to overcome evaluative dichotomies and to think about morality from new perspectives. Although Fouillée's work on Nietzsche was published more than a century ago, one can observe, to this day, the persistence of readings that reduce the complexity and exuberance of Nietzsche's thought to the image of a demented, egotistical, aggressive and militaristic philosopher. Our research demonstrates that reading Fouillée is not an isolated case in France. For this reason, in the first chapter, we explore general aspects of the context of reception of Nietzsche's work on French soil, also presenting Fouillée's main criticisms of Nietzsche's doctrines and the opposition between Nietzsche and Guyau. In the second chapter, we address the notions of selfishness and altruism in Nietzsche's thought, as well as the criticisms he directed at utilitarians — such as Jeremy Bentham, John Stuart Mill and Herbert Spencer — who, according to the philosopher, would not have been able to question "the value of values" and, consequently, to face the real problem of morality. The third chapter consists of an analysis of Jean-Marie Guyau's moral ideas, especially those related to selfishness and altruism. To distance ourselves from the reading of Fouillée and the role he attributes to the young philosopher as the antipode of Nietzsche, we take as a basis the works of Guyau himself, as well as the notes left by Nietzsche about his writings. Finally, in the fourth chapter, we deal with Nietzschean immoralism and its connection with the task of transvaluing all values. In this same chapter, we focus on the analysis of Fouillée's interpretation, with the aim of verifying whether it does justice to the effective purposes of Nietzsche's thought.